The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10162-015-0548-2
|View full text |Cite
|
Sign up to set email alerts
|

Pitch Discrimination in Musicians and Non-Musicians: Effects of Harmonic Resolvability and Processing Effort

Abstract: Musicians typically show enhanced pitch discrimination abilities compared to non-musicians. The present study investigated this perceptual enhancement behaviorally and objectively for resolved and unresolved complex tones to clarify whether the enhanced performance in musicians can be ascribed to increased peripheral frequency selectivity and/or to a different processing effort in performing the task. In a first experiment, pitch discrimination thresholds were obtained for harmonic complex tones with fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 21 publications
6
35
2
Order By: Relevance
“…For example, musicians show superior performance for gap detection (Zendel and Alain, 2012) and temporal-interval discrimination (Banai et al, 2012). This is consistent with the idea that musicians have generally greater proficiency in making use of the available neural information, as well as having enhanced neural coding (Banai et al, 2012), perhaps because of enhanced auditory attention (Strait et al, 2010;Bianchi et al, 2016). It is also possible that musicians were better than non-musicians at ignoring the false cue mentioned above, but, as stated earlier, the better performance with the modified version than with the standard version of the TFS1 test suggests that the negative influence of the false cue was very small.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…For example, musicians show superior performance for gap detection (Zendel and Alain, 2012) and temporal-interval discrimination (Banai et al, 2012). This is consistent with the idea that musicians have generally greater proficiency in making use of the available neural information, as well as having enhanced neural coding (Banai et al, 2012), perhaps because of enhanced auditory attention (Strait et al, 2010;Bianchi et al, 2016). It is also possible that musicians were better than non-musicians at ignoring the false cue mentioned above, but, as stated earlier, the better performance with the modified version than with the standard version of the TFS1 test suggests that the negative influence of the false cue was very small.…”
Section: Discussionsupporting
confidence: 66%
“…Several studies have shown that musicians perform better than nonmusicians in pitch-related tasks, including F0 discrimination (Kishon-Rabin et al, 2001;Micheyl et al, 2006). Furthermore, musicians perform better than non-musicians for complex tones containing both resolved harmonics and high unresolved harmonics (Bianchi et al, 2016;Bianchi et al, 2017). However, it is not clear whether musicians are better than non-musicians in using TFS cues for F0 discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to match the tinnitus pitch to an external sound varies greatly from person to person. Musically gifted or trained individuals naturally perform better in frequency discrimination and pitch matching than "nonmusical" subjects [Beckett and Haggard, 1973;Spiegel and Watson, 1984;Kishon-Rabin et al, 2001;Tervaniemi et al, 2005;Bianchi et al, 2016]. For nonmusician patients, the acoustics-related concepts and terminology used during tinnitus pitch matching are often unfamiliar and confusing, which leads to errors such as octave confusion, or simply to wrong pitch estimates.…”
Section: Computer-based Tinnitus Pitch Matchingmentioning
confidence: 99%
“…Pitch is a prominent quality of sound important for music and speech, the object of keen interest since antiquity (de Cheveign e, 2005;Plack, 2010;McDermott and Oxenham, 2008;Oxenham, 2012). Pitch discrimination has been explored in many studies, to characterize perceptual and sensory limits (Moore, 1973;Bernstein and Oxenham, 2003;Demany et al, 2009;Oxenham et al, 2011;Micheyl et al, 2012;Micheyl et al, 2010a) in the psychophysical tradition, to explore effects of context or memory (Matthews and Stewart, 2008;Ries and DiGiovanni, 2009;Nahum et al, 2010;Raviv et al, 2012;Mathias et al, 2010;Micheyl et al, 2010b), to characterize interindividual differences (Semal and Demany, 2006;Mathias et al, 2010) and to relate them to factors such as musicianship (Kishon-Rabin et al, 2001;Nikjeh et al, 2008;Peretz et al, 2002;Micheyl et al, 2006;Tervaniemi et al, 2005;Bianchi et al, 2016), intellectual abilities or impairment (Acton and Schroeder, 2001;Parsons et al, 2009), effects of training and plasticity (Demany and Semal, 2002;Carcagno and Plack, 2011b;Micheyl et al, 2006;Goldsworthy and Shannon, 2014;Carcagno and Plack, 2011a), or electrophysiological responses (Nikjeh et al, 2008;Barker et al, 2011;Carcagno and Plack, 2011a;...…”
Section: Introductionmentioning
confidence: 99%
“…The frequency difference is varied adaptively to converge on the threshold (usually corresponding to 70.7% or 79% correct). Other studies have used 3 tones (Bernstein and Oxenham, 2003;Kishon-Rabin et al, 2001;Nikjeh et al, 2008;Bianchi et al, 2016) or 4 tones (Semal and Demany, 2006;Mathias et al, 2010;Amitay et al, 2006) per trial.…”
Section: Introductionmentioning
confidence: 99%